Facklamia hominis pyelonephritis in a pediatric patient: first case report and review of the literature - Samantha Pérez-Cavazos; Daniela Cisneros-Saldaña; Fernando Espinosa-Villaseñor; José Iván Castillo-Bejarano; Denisse Natalie Vaquera-Aparicio; Hugo Sánchez-Alanís; Abiel Mascareñas-De los Santos (BMC, 2022)
Abstract Background Pyelonephritis is one of the most serious bacterial illnesses during childhood. Gram-negative organisms account for up to 90% of the cases. Gram-positive bacteria are uncommon causes of urinary tract infections, and only a few cases caused by Facklamia hominis have been reported in the literature. Case presentation A five-year-old girl with tracheostomy and gastrostomy and past medical history of congenital lymphangioma presented with a two-week history of with intermittent fever, frequent urination, and vesical tenesmus. Diagnosis of pyelonephritis was made. Urine culture reported colonies with alpha-hemolysis in blood agar at 48-h of incubation and Facklamia hominis was identified by MALDI-TOF. The patient was successfully treated with gentamicin. Conclusions This is the first reported case of pyelonephritis by Facklamia hominis in a child, and the second involving infection in a pediatric patient. Although this pathogen is uncommon, current treatment of F. hominis is a challenge for physicians. This case illustrates the requirement to standardize identification and treatment of care to avoid treatment failure and antimicrobial resistance.